2011
DOI: 10.1093/annonc/mdq464
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and endometrial cancer risk

Abstract: This study indicates a direct association between various MetS components, besides overweight, with the risk of endometrial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(114 citation statements)
references
References 39 publications
7
105
0
2
Order By: Relevance
“…Endogenous estrogen exposure has also been cited. Direct associations between the metabolic syndrome and its individual components and endometrial cancer risk have been previously described [48]. Brancati, et al [39] reported that Blacks suffer a two-fold increased risk of diabetes when compared with Whites, even when controlling for the usual surrogates for obesity, BMI and waist-to-hip ratio.…”
Section: Discussionmentioning
confidence: 94%
“…Endogenous estrogen exposure has also been cited. Direct associations between the metabolic syndrome and its individual components and endometrial cancer risk have been previously described [48]. Brancati, et al [39] reported that Blacks suffer a two-fold increased risk of diabetes when compared with Whites, even when controlling for the usual surrogates for obesity, BMI and waist-to-hip ratio.…”
Section: Discussionmentioning
confidence: 94%
“…In diabetic patients, the increased levels of oestrogen and androgen and the decreasing level of progesterone are considered potentially carcinogenic conditions for the breast, endometrium and ovaries. Hyperinsulinism also indirectly produces changes in sex hormone-binding globulin (SHBG) levels, including increases in the levels of oestrogen [69]. High BMI (and hyperadiponectinemia) and non-alcoholic fatty liver may also increase circulating SHBG [70,71].…”
Section: Discussionmentioning
confidence: 99%
“…Originally, the concern regarding metabolic syndrome was primarily focused on its contribution to increased cardiovascular disease and type 2 diabetes mellitus risk. However, recent evidence has shown a carcinogenic role of the metabolic syndrome in certain types of cancer [6][7][8][9][10][11]. However to date, epidemiological studies on metabolic syndrome and gastroesophageal cancer are sparse.…”
Section: Introductionmentioning
confidence: 99%